Labour market deregulation and apprenticeship training : a comparison of German and Swiss employers - Jansen, Anika [Verfasser]; Strupler Leiser, Mirjam [Verfasser]; Wenzelmann, Felix [Verfasser]; Wolter, Stefan C. [Verfasser] (My University, 2015)
"Many extensions of classical human capital theory regard labour market rigidities as a prerequisite for firms to invest in general training. From this perspective, the German labour market reforms since 2003 should have reduced their willingness to support the apprenticeship training system. This article demonstrates that, on the contrary, German firms did not abandon the training system but instead changed their training strategies after the implementation of the labour market reforms. We analyse the new training strategies that German firms deployed to cope with the increased labour market flexibility engendered by the labour market reforms. Switzerland, where no such reforms occurred, serves as the counterfactual. The results demonstrate that German firms successfully reduced the net costs of training by involving apprentices in more work and reducing non-productive tasks." (Authors' abstract, BIBB-Doku)
Version of Record - Nov 27, 2015. - OnlineFirst Version of Record - Apr 14, 2015.
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 4 Kosten & Finanzierung; G 1.2 Arbeitsmarkt; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.2.1 Westeuropa; Arbeitsmarkt; Regulierung; Ausbildungsangebot; Berufsausbildung; Ausbildungsqualität; Ausbildungsverhalten; Betrieb; Finanzierung; Ausbildungsinvestition; Kosten-Nutzen-Analyse; Internationaler Vergleich; Schweiz; Bundesrepublik Deutschland